(untitled) (Research, Society and Development, 2022)
Assessing the natural vulnerability to aquifer contamination is a relevant instrument for protecting the quality of groundwater water, as well as helping to manage local water resources. This research aimed to analyze and map the natural vulnerability to contamination of the aquifer of Island de Colares - PA, using the GOD (Groundwater occurrence, Overall Lithology of the unsaturated zone, Depth of the water table) method, as well as to identify potential sources of contamination. The application of the GOD method made it possible to map the degree of vulnerability and the method of environmental impact assessment, checklist (checklist) provided the survey of potential sources of contamination. The results indicated that the medium vulnerability class was more representative with 95.49% (44.10 km²), followed by the low vulnerability class with 2.59% (1.20 km²) and high vulnerability to contamination 1.92% (0.89 km²). The predominance of the middle class of vulnerability in the study area raises a concern, but mainly due to the presence of a potential source of contamination located in an area with a high degree of vulnerability, as well as due to the direction of the underground flow. The results of the analysis of the physicochemical parameters revealed that they are in accordance with Ordinance GM/MS n. º 888/2021, which defines the potability of water and CONAMA Resolution n.º 396/2008. Finally, it is concluded that the elaboration of the map of natural vulnerability to aquifer contamination can contribute to the diagnosis of groundwater quality and to assist in the management and conservation of water.